IMPLEMENTATION OF TWO LANGUAGE CHATBOT WEB TO FIND INFORMATION ON BATIK USING THE ARTIFICIAL NEURAL NETWORK MODEL - Taufik Maulana Tanjung; Rahmat Hidayat (TEKNOKOM, 2023)
Information technology plays an important role in the progress of a country in order to disseminate information massively and make it easier for the public to obtain information. Currently, the development of information technology continues to innovate, such as with the existence of artificial intelligence (AI) technology. This research will discuss AI technology, namely the BatikInd chatbot with the artificial neural network (ANN) method, which aims to make it easier for people to find information about the types of batik that, exist in all regions of Indonesia. The design of the ANN method for making chatbots uses hundreds of sentences to be processed into a database of information about the types of batik and explanations about the batik you want to find. Database processing with epochs reaching 200 produces an accuracy rate of 1.0 (100%) which means the accuracy rate is very good and the error rate reaches 0.03 (0%) which means the error rate is very low. The results of a very good level of accuracy and a very low error rate indicate that this AI can function properly and is feasible to use. It is hoped that with information technology like this, it will make it easier for people to find information about batik and can increase people's literacy and knowledge about batik in all regions of Indonesia.